Akar Gerakan Teologi Politik Fundamentalisme Islam Abad Modern Perspektif Karen Armstrong - Rohmatul Izad (Islamika Inside: Jurnal Keislaman dan Humaniora, 2018)
The article analyzes the root of political movement of Islamic fundamentalism in the modern era with particular focus on tracing theological and political reason of this group in Karen Armstrong's work. The author tries to critically discuss Armstrong's views about political ideology held by the Islamic fundamentalism. Since the Islamic fundamentalism needs to be carefully understood as a political movement, it can help us to clearly identify their position along with their ideological basis they fight for. This study concludes that various types and forms of what so-called "fundamentalism" should be essentially observed as political-theological discourse; a sort of nationalism or ethnicity which is articulated in religiously manner. Therefore, fundamentalism can be understood as a political movement based on Islamic ideology. Furthermore, the theology and ideology of fundamentalists have been psychologically rooted from fear and anxiety. It has been a result of their assumption that the proponents of secularism would annihilate them. The fundamentalism is not an obsolete matter from the past; rather it is a modern and innovative movement.